Multimodal neuroimaging of metabotropic glutamate 5 receptors and functional connectivity in alcohol use disorder. (21st April 2022) - Smart, Kelly; Worhunsky, Patrick D.; Scheinost, Dustin; Angarita, Gustavo A.; Esterlis, Irina; Carson, Richard E.; Krystal, John H.; O'Malley, Stephanie S.; Cosgrove, Kelly P.; Hillmer, Ansel T.
Abstract: Background: People recovering from alcohol use disorder (AUD) show altered resting brain connectivity. The metabotropic glutamate 5 (mGlu5) receptor is an important regulator of synaptic plasticity potentially linked with synchronized brain activity and a target of interest in treating AUD. The goal of this work was to assess potential relationships of brain connectivity at rest with mGlu5 receptor availability in people with AUD at two time points early in abstinence. Methods: Forty‐eight image data sets were acquired with a multimodal neuroimaging battery that included resting‐state functional magnetic resonance imaging (fMRI) and mGlu5 receptor positron emission tomography (PET) with the radiotracer [ 18 F]FPEB. Participants with AUD ( n = 14) were scanned twice, at approximately 1 and 4 weeks after beginning supervised abstinence. [ 18 F]FPEB PET results were published previously. Primary comparisons of fMRI outcomes were performed between the AUD group and healthy controls (HCs; n = 23) and assessed changes over time within the AUD group. Relationships between resting‐state connectivity measures and mGlu5 receptor availability were explored within groups. Results: Compared to HCs, global functional connectivity of the orbitofrontal cortex was higher in the AUD group at 4 weeks of abstinence ( p = 0.003), while network‐level functional connectivity within the default mode network (DMN) was lower ( p < 0.04). Exploratory multimodal analyses showed that mGlu5 receptor availability was correlated with global connectivity across all brain regions (HCs, r = 0.41; AUD group at 1 week of abstinence, r = 0.50 and at 4 weeks, r = 0.46; all p < 0.0001). Furthermore, a component of cortical and striatal mGlu5 availability was correlated with connectivity between the DMN and salience networks in HCs ( r = 0.60, p = 0.003) but not in the AUD group ( p > 0.3). Conclusions: These preliminary findings of altered global and network connectivity during the first month of abstinence from drinking may reflect the loss of efficient network function, while exploratory relationships with mGlu5 receptor availability suggest a potential glutamatergic relationship with network coherence. Abstract : The Metabotropic Glutamate 5 (mGlu5) Receptor is an important regulator of synaptic plasticity implicated in alcohol drinking behaviors. This study performed mGlu5 receptor positron emission tomography imaging and resting state functional magnetic resonance imaging in people with alcohol use disorder (AUD) during abstinence. Novel multimodal analyses revealed relationships between mGlu5 receptor availability and functional networks in controls that were absent in AUD subjects, providing preliminary evidence for glutamatergic relationships with functional network coherence that are disrupted in AUD.